The Use of Kahoot! as Formative Assessment in Education - Bernadetha Wahyu Widyaningrum (Indonesian Journal of English Language Studies (IJELS), 2019)
Technology appears as one of the significant tools to create a meaningful process in all fields of life for living things, one of which is education. This situation drives related parties to create game-based learning platform for education. One of the emerging game-based learning platform used in education is Kahoot!. Educationally relevant game, such as Kahoot! makes students learn academic content with a lot of excitement. Recently, Kahoot! is used as a tool for formative assessment. Formative assessment is useful to improve students’ attainment. This study aims to investigate the effectiveness of Kahoot! used as formative assessment in education. This paper will elaborate the theoretical review as well as the application that underlay the hypothesis. The result of the study shows that Kahoot! is an alternative tool of interactive formative assessment. Kahoot! is feasible and practical to make learning fun and enjoyable because it has many benefits for education.